The Development of Digital Textbooks 来学汉语lái xué Hànyǔ based on the 2013 Curriculum Cross-Major Courses of Mandarin for the Tenth Graders - Sulistyo, Asmania Rizki Nurjannah; Mintowati, Maria; Suyatno, Suyatno (International Journal for Educational and Vocational Studies, 2020)
Based on the observations of the use of textbooks in teach Mandarin, the identification sheet of students' needs and the results of interviews with Mandarin teachers found several problems. Among them, the majority of teachers still use imported textbooks from China, the contents of textbooks that do not reflect Indonesian culture and are not in accordance with the 2013 Curriculum, have not been sufficient to provide exercises for the practice of language skills, the order of material that has not been arranged in accordance with the rules for the preparation of textbooks, the number of textbooks available is limited, the condition of textbooks whose time has expired, and the learning process is less active and teacher-centered. This study aimed to examine the process of developing Mandarin digital textbooks in terms of the quality, effectiveness and practicality of 2013 curriculum-based digital textbooks in across-major courses of Mandarin for tenth graders. This development research uses Sugiyono's development model. This development research was carried out on the class X IPA 4 SMA Dharma Wanita Surabaya. The results of the validation of Mandarin textbook material are 89%, the results of the validation are 87%, the results of the language validation are 85%, and the results of the validation are 92%. All validation results are in the "very strong" category. The results of observations of student and teacher activities are 89% for student activities and 87% for teacher activities. The t-significance calculation uses a 95% confidence level or a 5% significance level and a t-significance result of 24, 11. This indicates that there are significant differences between the pre-test and post-test scores. It is said that Mandarin textbooks are effective for use